Integrating Islamic Values In The Development Of The Merdeka Campus Curriculum: Enhancing Student Independence In Islamic Higher Education - Akhyak; Sahri; Agus Eko Sujianto; Binti Maunah; Agus Zaenul Fitri; Ahmad Tanzeh (Pondok pesantren As-salafiyah As-Safi'iyyah, 2026)
Islamic university students today face serious challenges in the form of low learning independence. Many of them still depend on their lecturers' guidance, lack initiative in exploring knowledge, and are not yet fully capable of managing their own learning independently. This study aims to examine how the development of the MBKM curriculum in PTKI can enhance students' learning independence and support the realization of impactful campuses. This research uses a qualitative approach with a case study design, conducted at Nahdlatul Ulama University Surabaya (UNUSA) and Yudharta University Pasuruan. Data collection techniques were carried out through in-depth interviews, observations, and documentation, with data analysis using data condensation, data presentation, conclusion drawing, and verification. The research results show that the development of the MBKM curriculum at both universities encourages students to learn actively, independently, and reflectively through programs such as internships, entrepreneurship, teaching on campus, and community service. Independent learning is reflected in students' ability to manage the learning process, make decisions, and take responsibility for their learning achievements. In addition, Islamic values also frame this process, resulting in learners who are not only academically excellent but also ethical and contribute significantly to society. Thus, the contextually developed MBKM curriculum has proven to be an important instrument in shaping independent students while also realizing an impactful campus.